Green, Yellow, and Red risk perception in everyday life – a communication tool - Stensgaard, A.; DunnGalvin, A.; Nielsen, D.; Munch, M.; Bindslev‐Jensen, C. (Allergy (Copenhagen), 2017)
Background Adolescents have the highest risk for food allergy‐related fatalities. Our main aim was to investigate the level of risk in everyday social situations as perceived by adolescents/young adults with peanut allergy, their families, and their friends. Methods The web‐based ‘Colours Of Risks’ (COR) questionnaire was completed by 70 patients (aged 12–23 years), 103 mothers and fathers, 31 siblings (aged 12–26 years), and 42 friends (aged 12–24 years). COR deals with six main contexts (home, school/university, work, visiting/social activities, special occasions/parties, and vacations), each with 1‐12 items. Response categories are green (I feel safe), yellow (I feel uncertain), or red (I feel everything is risky). Results There was a high level of agreement between participants in defining situations as safe, uncertain, or risky, but female patients and mothers rated fewer situations as safe compared to male patients and fathers. Being with close friends and family, and attending planned parties without alcohol were perceived as situations of low risk. While 94% of patients took an epinephrine auto‐injector (EAI) into risky situations, only 65% took it into safe situations. In contrast to the close family, 31% of the friends did not know the patient had an EAI, and fewer knew how to administer the EAI. Conclusion Young adults with peanut allergy face challenges when moving from the safe home with ready assistance if needed, to independence with unpredictable surroundings and less certain help. Perceived ‘safe’ situations may in fact be the riskiest, as patients often do not take the EAI with them.